Impact of Obesity on Orthodontic Tooth Movement in Adolescents: A Prospective Clinical Cohort Study. (May 2017) - Saloom, H.F.; Papageorgiou, S.N.; Carpenter, G.H.; Cobourne, M.T.
Obesity is a widespread chronic inflammatory disorder characterized by an increased overall disease burden and significant association with periodontitis. The aim of this prospective clinical cohort study was to investigate the effect of obesity on orthodontic tooth movement. Fifty-five adolescent patients (27 males, 28 females) with a mean (SD) age of 15.1 (1.7) years and mean (SD) body mass index (BMI) of 30.2 (3.5) kg/m 2 in obese and 19.4 (2.2) kg/m 2 in normal-weight groups were followed from start of treatment to completion of tooth alignment with fixed orthodontic appliances. Primary outcome was time taken to complete tooth alignment, while secondary outcomes included rate of tooth movement and change in clinical parameters (plaque/gingival indices, unstimulated whole-mouth salivary flow rate, gingival crevicular fluid biomarkers). Data collection took place at baseline (start of treatment: appliance placement), 1 h and 1 wk following appliance placement, and completion of alignment. Results were analyzed by descriptive statistics followed by generalized estimating equation regression modeling. There were no significant differences between groups in time taken to achieve tooth alignment (mean [SD] 158.7 [75.3] d; P = 0.486). However, at 1 wk, initial tooth displacement was significantly increased in the obese group ( P < 0.001), and after adjusting for confounders, obese patients had a significantly higher rate of tooth movement compared with normal-weight patients (+0.017 mm/d; 95% confidence interval, 0.008–0.025; P < 0.001) over the period of alignment. Explorative analyses indicated that levels of the adipokines leptin and resistin, the inflammatory marker myeloperoxidase (MPO), and the cytokine receptor for nuclear factor kappa-B ligand (RANKL) were significantly different between obese- and normal-weight patients and associated with observed rates of tooth movement. This represents the first prospective data demonstrating a different response in obese patients compared with normal-weight patients during early orthodontic treatment. These differences in the response of periodontal tissues to orthodontic force in the presence of obesity have potential short- and long-term clinical implications.